# Bài 94 trang 131 SGK giải tích 12 nâng cao

##### Hướng dẫn giải

\eqalign{ & a)\,\,{\log _3}\left( {\log _{0,5}^2x - 3{{\log }_{0,5}}x + 5} \right) = 2 \Leftrightarrow \log _{0,5}^2x - 3{\log _{0,5}}x + 5 = 9 \cr & \Leftrightarrow \log _{0,5}^2x - 3{\log _{0,5}x} - 4 = 0 \Leftrightarrow \left[ \matrix{ {\log _{0,5}x} = - 1 \hfill \cr {\log _{0,5}x} = 4 \hfill \cr} \right. \cr & \Leftrightarrow \left[ \matrix{ x = {\left( {0,5} \right)^{ - 1}} = 2 \hfill \cr x = {\left( {0,5} \right)^4} = {1 \over {16}} \hfill \cr} \right. \cr}

Vậy $$S = \left\{ {2;{1 \over {16}}} \right\}$$

b) Ta có: $${\log _2}\left( {{{4.3}^x} - 6} \right) - {\log _2}\left( {{9^x} - 6} \right) = 1 \Leftrightarrow {\log _2}\left( {{{4.3}^x} - 6} \right) = {\log _2}2\left( {{9^x} - 6} \right)$$

$$\Leftrightarrow \left\{ \matrix{ {9^x} - 6 > 0 \hfill \cr {4.3^x} - 6 = 2\left( {{9^x} - 6} \right) \hfill \cr} \right. \Leftrightarrow \left\{ \matrix{ t > \sqrt 6 \hfill \cr 2{t^2} - 4t - 6 = 0 \hfill \cr} \right.$$ (với $$t = {3^x}$$)

$$\Leftrightarrow t = 3 \Leftrightarrow {3^x} = 3 \Leftrightarrow x = 1$$

Vậy $$S = \left\{ 1 \right\}$$
c) Điều kiện: $$x >9$$

\eqalign{ & 1 - {1 \over 2}\log \left( {2x - 1} \right) = {1 \over 2}\log \left( {x - 9} \right) \Leftrightarrow 2 = \log \left( {2x - 1} \right) + \log \left( {x - 9} \right) \cr & \Leftrightarrow \log \left( {2x - 1} \right)\left( {x - 9} \right) = 2 \Leftrightarrow \left( {2x - 1} \right)\left( {x - 9} \right) = 100 \cr & \Leftrightarrow 2{x^2} - 19x - 91 = 0 \Leftrightarrow \left[ \matrix{ x = 13 \hfill \cr x = - 3,5\,\,\left( \text {loại} \right) \hfill \cr} \right. \cr}

Vậy $$x=13$$

d) Điều kiện: $$x > 2$$

Ta có: $${\log _{{1 \over 8}}}\sqrt {3x - 5} = {\log _{{2^{ - 3}}}}{\left( {3x - 5} \right)^{{1 \over 2}}} = - {1 \over 6}{\log _2}\left( {3x - 5} \right)$$
Phương trình đã có trở thành:

\eqalign{ & {1 \over 6}{\log _2}\left( {x - 2} \right) + {1 \over 6}{\log _2}\left( {3x - 5} \right) = {1 \over 3} \cr & \Leftrightarrow {\log _2}\left( {x - 2} \right)\left( {3x - 5} \right) = 2 \cr & \Leftrightarrow \left( {x - 2} \right)\left( {3x - 5} \right) = 4 \cr & \Leftrightarrow x = 3\,\,\text{ hoặc }\,\,x = {2 \over 3}. \cr}

Với điều kiện $$x > 2$$ ta chỉ nhận nghiệm $$x = 3$$.
Vậy $$S = \left\{ 3 \right\}$$